The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1007/978-3-642-31095-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Business Process Models: The Costs and Benefits of Structuredness

Abstract: Abstract. Previous research has put forward various metrics of business process models that are correlated with understandability. Two such metrics are size and degree of (block-)structuredness. What has not been sufficiently appreciated at this point is that these desirable properties may be at odds with one another. This paper presents the results of a twopronged study aimed at exploring the trade-off between size and structuredness of process models. The first prong of the study is a comparative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
(44 reference statements)
1
40
0
2
Order By: Relevance
“…Mendling and Strembeck (2008, p. 147), who calculate the metric as ''one minus the number of nodes in structured blocks divided by the number of nodes,'' find no significant correlation between it and comprehension accuracy. Dumas et al (2012) find that a comparable metric results in inconsistent results, as structuredness reduces comprehension for two models and heightens comprehension in two other models, which leads the authors to conclude that structuring might be beneficial only when it does not increase the number of gateways.…”
Section: Modularity/structurednessmentioning
confidence: 80%
“…Mendling and Strembeck (2008, p. 147), who calculate the metric as ''one minus the number of nodes in structured blocks divided by the number of nodes,'' find no significant correlation between it and comprehension accuracy. Dumas et al (2012) find that a comparable metric results in inconsistent results, as structuredness reduces comprehension for two models and heightens comprehension in two other models, which leads the authors to conclude that structuring might be beneficial only when it does not increase the number of gateways.…”
Section: Modularity/structurednessmentioning
confidence: 80%
“…There is no clear definition of the notion of understanding of business process models. It is used in different manners depending on the context [1], [2], [3], [4]. Even though a definition lacks, this notion is very important.…”
Section: Process Model Understandingmentioning
confidence: 99%
“…In practice, making a model structured without duplication appears to be rather rare. An investigation with more than 500 models from practice has shown that structuring leads to an increase in size of about 50% on average [53]. It is also important to note that duplication might be more harmful than a usual increase in size.…”
Section: Refactoring the Structure Of Process Modelsmentioning
confidence: 99%
“…It is also important to note that duplication might be more harmful than a usual increase in size. The user experiment reported in [53] points to a potential confusion by model readers who are asked about behavioural constraints that involve activities that are shown multiple times in the model.…”
Section: Refactoring the Structure Of Process Modelsmentioning
confidence: 99%